2012
DOI: 10.1002/ejoc.201200406
|View full text |Cite
|
Sign up to set email alerts
|

Aziridines in Formal [3+2] Cycloadditions: Synthesis of Five‐Membered Heterocycles

Abstract: Chemistry based on ring opening of aziridines has been widely studied in organic synthesis. However, it has mainly been centered on ring opening by nucleophiles and on cycloaddition of azomethine ylides generated by carbon–carbon bond cleavage. In recent years, significant effort has been dedicated to study of the participation of aziridines in formal [3+2] cycloadditions, which provide routes for the construction of a wide variety of functionalized five‐membered heterocycles. Here we review the most relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(32 citation statements)
references
References 69 publications
0
31
0
1
Order By: Relevance
“…However, under these conditions, optically active aziridine undergoes coupling to give the target heterocycle in 36% ee. The drop in the enantiomeric purity may presumably due to a partial involvement of S N 1 pathway along with S N 2 ,. Development of the catalytic methods to access enantiomerically enriched scaffolds would thus be valuable.…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 99%
“…However, under these conditions, optically active aziridine undergoes coupling to give the target heterocycle in 36% ee. The drop in the enantiomeric purity may presumably due to a partial involvement of S N 1 pathway along with S N 2 ,. Development of the catalytic methods to access enantiomerically enriched scaffolds would thus be valuable.…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 99%
“…Among them, the transition‐metal‐catalyzed [3+2] cycloadditions of aziridines represent powerful tools enabling quick and efficient access to pyrrolidines in an atom‐economical fashion. However, almost all previous studies on this topic have been focused on 1,3‐dipolar cycloadditions of either aryl or alkyl aziridines by selective C−C, and C−N bond cleavage with alkynes or alkenes for the formation of pyrrolidine derivatives, substituted with saturated C−C bonds, in racemic form. In contrast, the [3+2] cycloaddition of an aziridine with an allene is rarely reported, and seriously limits the utilization of this method in the synthesis of the valuable 2‐methylene‐ and 3‐methylene‐pyrrolidines containing a C=C bond .…”
Section: Figurementioning
confidence: 99%
“…[178][179] The first breakthroughs were reported in 1999. Bergmeier and co-workers demonstrated that the intramolecular cycloaddition of tosyl aziridines and allyl silanes could be catalyzed by boron-trifluoride etherate (Scheme 7.28, A).…”
Section: Formal [3+1] Cycloadditionsmentioning
confidence: 99%